Larger striatal volume is associated with increased adult psychopathy - Choy, Olivia (2022)
Prior studies have inconsistently reported increased volumes of the striatum in adults with psychopathy. A meta-analysis presented here indicates an overall effect size of d = 0.44. Nevertheless, variability in findings exist, and questions remain on confounding clinical conditions and generalizability to females. This study tests the hypothesis that striatal volumes are increased in adults with psychopathic traits, and that this relationship is mediated by stimulation-seeking and impulsivity. Striatal volume was assessed using magnetic resonance imaging in 108 adult community-dwelling males alongside psychopathy using the Psychopathy Checklist - Revised. Subsidiary, exploratory analyses were conducted on a small sample of females. Correlational analyses showed that increased striatal volumes were associated with more psychopathic traits (p = .001). Effects were observed for all striatal regions, controlling for age, substance dependence and abuse, antisocial personality disorder, attention deficit hyperactivity disorder, social adversity, and total brain volume. An analysis of 18 psychopathic individuals showed that striatal volumes were increased 9.4% compared with 18 matched controls (p = .01). Psychopathy in females was also significantly associated with increased striatal volume (p = .02). Stimulation-seeking and impulsivity partly mediated the striatal-psychopathy relationship, accounting for 49.4% of this association. Findings from these two samples replicate and build on initial studies indicating striatal enlargement in adults with psychopathy, yielding an updated effect size of d = 0.48. Results are consistent with the notion that striatal abnormalities in individuals with psychopathy partly reflect increased sensation-seeking and impulsivity, and support the hypothesis of abnormal reward processing in psychopathy.